An interview study to explore the perceived usefulness of in-house training programs in tourism and hospitality education. Issue 12 (December 2022) - Fuchs, Kevin
Abstract: COVID-19 has accelerated the adoption of online teaching and learning modes. It has also abruptly changed the traditional teaching and learning methods that originally relied on physical attendance, including student internships. In-house training programs were launched by the university to offer students an alternative to their regular internships. The study is designed to investigate how university students in tourism and hospitality education perceive the usefulness of their in-house training in absence of industry placements. An exploratory methodological approach was adopted by conducting 25 semi-structured in-depth interviews with student interns to understand their experiences during the in-house training. The empirical findings revealed that the in-house program, in its current state, is not to be considered a permanent alternative for tourism and hospitality undergraduate students. The article concludes by presenting implications for educators, policymakers, and education researchers derived from the academic and practical discussions based on the findings. Abstract : Higher education; COVID-19; Competency development; Tourism and hospitality education; Undergraduate; Internships.